A Biomechanical Analysis of Treatment Options for Enchondromas of the Hand. (March 2013) - Pianta, Teresa J.; Baldwin, Paul S.; Obopilwe, Elifho; Mazzocca, Augustus D.; Rodner, Craig M.; Silverstein, Eric A.
Purpose: Enchondromas are the most common benign bone tumor affecting the hand. Standard treatment has consisted of curettage with bone grafting. It has become increasingly common for surgeons to use biologic cement in these cases. The purpose of this study was to evaluate different treatment options used to fill voids after curettage of hand enchondromas to determine if any provide more rigid fixation. Methods: A cadaveric model of hand enchondromas was designed by making a standardized size corticotomy (0.6×1.0 cm) in 60 cadaver metacarpals. Resultant voids were then filled with either no material, bovine demineralized bone matrix (Synthes Paoli, PA, USA), or one of two different calcium phosphate bone cements: a carbonated apatite (Synthes Norian SRS Skeletal Repair System) and a hydroxyapatite (Stryker HydroSet) calcium phosphate. An apex dorsal three-point bend was applied to the metacarpals through an MTS machine, and load to failure and stiffness were recorded. Results: Biomechanically, load to failure for intact metacarpals was significantly superior to those in which a corticotomy was created ( p =0.04). There was a significant increase in load to failure between the metacarpals treated with the calcium phosphate bone cement and the negative controls ( p =0). Conclusions: In a biomechanical analysis of a cadaveric model of hand enchondromas, calcium phosphate bone cement provided significantly increased strength as compared to curettage alone and approximated the strength of intact metacarpals. It is unknown whether the use of biologic cements in this clinical setting leads to less postoperative immobilization, earlier digital motion, a quicker return to work, or increased patient satisfaction.